Happs - Cawthon, Scott; Cooper, Elley; Waggener, Andrea (Five nights at Freddy's. Tales from the Pizzaplex, 2022)
Have you ever wanted something badly, even though you shouldn’t? . . . Steve’s dreams of a video game programming career and starting a family lead him to take a job that seems too good to be true. Aiden and Jace can’t resist scaring some young kids in the tube maze of Freddy Fazbear’s Mega Pizzaplex. And all Billy wants is to become the perfect ideal of what he knows he really is―an animatronic. But in the world of Five Nights at Freddy's, be careful what you wish for . . . In this second volume, Five Nights at Freddy's creator Scott Cawthon spins three sinister novella-length tales from uncharted corners of his series' canon.